Antibacterial apple cider vinegar eradicates methicillin resistant Staphylococcus aureus and resistant Escherichia coli - Darshna Yagnik (Nature Portfolio, 2021)
Abstract Methicillin-resistant Staphylococcus aureus (MRSA) and resistant Escherichia coli (rE.coli) infections can spread rapidly. Further they are associated with high morbidity and mortality from treatment failure. Therapy involves multiple rounds of ineffective antibiotics alongside unwanted side effects, alternative treatments are crucial. Apple cider vinegar (ACV) is a natural, vegan product that has been shown to have powerful antimicrobial activity hence we investigated whether ACV could ameliorate these resistant bacteria. The minimum dilution of ACV required for growth inhibition was comparable for both bacteria (1/25 dilution of ACV liquid and ACV tablets at 200 µg/ml were effective against rE. coli and MRSA). Monocyte co-culture with microbes alongside ACV resulted in an increase in monocyte phagocytosis by 21.2% and 33.5% compared to non-ACV treated but MRSA or rE. coli stimulated monocytes, respectively. Label free quantitative proteomic studies of microbial protein extracts demonstrated that ACV penetrated microbial cell membranes and organelles, altering the expression of key proteins. This resulted in significant reductions in total protein expression, moreover we could only detect ribosomal proteins; 50 s 30 s, enolase, phosphenol pyruvate and the ATP synthase subunit in rE. coli. Elongation factor iNOS and phosphoglycerate kinase OS were the only proteins present in MRSA samples following ACV treatment.